TINDAK PIDANA PENCUCIAN UANG DAN TINDAK PIDANA KORUPSI PASKA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 77/PUU-XII/2014 - A Ira Fadilla Rohmadanti; Prija Djatmika; Yuliati, Yuliati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The application to the Constitutional Court with the Constitutional Court decision number 77/PUU-XII/2014 was based on the dissinting opinion of Hakum Alecander Mawarta in the TPPU case of the Central Jakarta District Court with Case Number 10.Pid.Sus-TPK/2014/PN.JKT.PST. Based on this judicial review, the Constitutional Court stated that the existence of Article 69 in Law No. 8/2010, which states that law enforcement officials are allowed to investigate, investigate and examine ML/TF cases without proving the original crime, is questionable because it is not in accordance with the characteristics of ML/TF as a continuation of the original crime. Thus, there are juridical implications that will occur related to the prevention of ML, among others: potential acquittal of the defendant; violation of the principle of presumption of innocence, contrary to the concept of proof adopted in Indonesia and so forth. Of course, in this research, the author will reconstruct the placement of the Money Laundering Crime as Independent Crimes along with its legal implications in practice. This is because the placement of the Money Laundering Crime as Independent Crimes has given legal consequences to the legal system adopted in Indonesia, one of which is the Presumption of Innocence. This research is a descriptive analytical literature research using juridical-normative approach and qualitative deductive method. In doing so, it is concluded that the development of ML has experienced increasingly complex developments and legal breakthroughs that place ML as a stand-alone criminal offence.